2012
DOI: 10.1002/ptr.4776
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Anticancer Effects of Wild Carrot Oil Extract

Abstract: Daucus carota L. ssp. carota (Apiacea) is used in traditional medicine in Lebanon and in different regions throughout the world. The present study investigates the in vitro anticancer activities of Daucus carota oil extract (DCOE) on four human cancer cell lines as well as its in vitro antioxidant activity. DCOE was extracted from the dried umbels with 50:50 acetone-methanol. The oil extract was analyzed by gas chromatography-mass spectrometry and screened for its antioxidant properties in vitro using 1,1-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 39 publications
1
51
1
Order By: Relevance
“…Microwaving did not alter the DPPH • scavenging capacity of carrots. Previous studies reported 0.18 mg trolox equivalents per mL of carrot oil (Shebaby et al., 2013), which is about 0.025 μmol trolox equivalent per gram of carrot seeds with a 3.47% oil.…”
Section: Resultsmentioning
confidence: 99%
“…Microwaving did not alter the DPPH • scavenging capacity of carrots. Previous studies reported 0.18 mg trolox equivalents per mL of carrot oil (Shebaby et al., 2013), which is about 0.025 μmol trolox equivalent per gram of carrot seeds with a 3.47% oil.…”
Section: Resultsmentioning
confidence: 99%
“…DCOE exhibited antioxidant activity in all assays. The FRAP value was 164 ± 5.5 µmol for FeSO 4 /g, and the IC 50 values for DPPH and FIC assays were 2.1 ± 0.03 mg/ml and 0.43 ± 0.02 mg/ml, respectively [109]. The antioxidant activity of the essential oils from the fruits of Daucus carota var.…”
Section: Antioxidant Effectmentioning
confidence: 92%
“…Oil extract caused significant increase in cell death and decrease in cell proliferation. The effects of the oil on cell lines were time and dose-dependent [109].In cytotoxic investigation of the essential oils from the fruits of Daucus carota var. sativus (yellow carrot) and var.…”
Section: Pharmacological Effects: Cytotoxic Effectsmentioning
confidence: 99%
“…Daucus carota L. (Apiacea) is traditionally used in different regions throughout the world for the treatment of gastric ulcer, diabetes, nephritic colic, cutaneous infections, and muscle pain (Jabrane et al, 2009;Shebaby et al, 2013). The in vitro anti-H. pylori properties of 60 different commercial essential oils were examined in a study.…”
Section: Daucus Carotamentioning
confidence: 99%